An Analysis of Islamic Senior High School English Teacher’s Perception of Using Code Switching in the Classsroom English Teaching - Herlina Emilda; Safnil Safnil; Ira Maisarah (English Education Study Program Faculty of Teacher Training and Education, 2021)
Although the teachers commonly used many languages in the classroom, but that doesn't guarantee avoiding code switching. This research explores the perceptions and beliefs of teachers regarding the use of code switching in Islamic Senior High School classrooms. It also examines the roles and functions of code switching in the classroom. The sample of this research was twenty two Islamic Senior High School English Teacher in Bengkulu were involved in this research. Data were collected through questionnaires and semi-structured interviews. The result from this research were, 1) Islamic Senior High School English teachers generally have positive and negative views about the practice of code switching in the classroom. 2) There were 25 reasons why do the teacher use code switching in the classroom, 3) The major function of teachers’ code switching mainly for curriculum access and for maintaining interpersonal relations. Furthermore, Teachers also would be well advised to have strategies for effectively managing code switching in the English Teaching classroom to avoid its negative implications on the language learning process. It can be concluded that teachers also used code switching to maintain interpersonal relations, specifically to encourage students’ participation in classroom activities, to increase students’ motivation in and confidence in learning the target language.